(untitled) (Bangladesh Journal of Medical Science, 2021)
Objective: Renal vascular thrombosis is a thrombotic blockage of the major renal arteries resulting in acute damage or chronic kidney disease. The study aims to analyze rare clinical cases of renal artery thrombosis with following renal infarction. Materials and methods: The article present a retrospective study of examination and treatment results of patients diagnosed with the renal arteries thrombosis in the urological hospital of the Irkutsk Clinical Hospital No. 1 in the period 2012-2020. Results and Discussion: During the entire observation period, there were two clinical cases of acute renal artery thrombosis. The 86-year-old woman developed thrombosis because of atrial fibrillation, which was probably the result of inadequate correction (insufficient dose of anticoagulant). Kidney infarction had complications like rapid suppuration because of chronic urinary infection and calculus of the renal pelvis. It resulted in nephrectomy with subsequent recovery. The second case was the 45-year-old man examined according to existing standards, and the diagnosed-on time in the first hours of the disease. However, complete thrombosis of the right renal artery neutralized the effectiveness of conservative therapy with warfarin. In this case, nephrosclerosis and renal failure were natural. Conclusion: Renal artery thrombosis is a rare pathology that requires special attention from the clinician due to the high risk of renal function loss. Timely diagnosis and correct treatment tactics are especially important. Bangladesh Journal of Medical Science Vol.20(3) 2021 p.550-555